Measurement of the t(t)over-bar production cross section in the tau plus jets channel in pp collisions at root s=7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Aguilo, E; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; et al. (2013)
The top-quark pair production cross section in 7 TeV center-of-mass energy proton-proton collisions is measured using data collected by the CMS detector at the LHC. The measurement uses events with one jet identified as a hadronically decaying τ lepton and at least four additional energetic jets, at least one of which is identified as coming from a b quark. The analyzed data sample corresponds to an integrated luminosity of 3.9 fb-1 recorded by a dedicated multijet plus hadronically decaying τ trigger. A neural network has been developed to separate the top-quark pairs from the W+jets and multijet backgrounds. The measured value of σtt̄= 152 ± 12,(stat.) ± 32,(syst.) ±,(lum.) pb is consistent with the standard model predictions. © 2013 CERN for the benefit of the CMS collaboration.